Building brand awareness for local skincare brand glad2glow: The role of UGC, testimonials, and audience engagement on tiktok - Efendi, Faturahman; Fauzi, Irsal (Trigin Publisher, 2026)
This study seeks to investigate the impact of User Generated Content (UGC) and testimonials on brand awareness, with engagement serving as a mediating variable, for the skincare company Glad2Glow on TikTok. This study utilizes a quantitative methodology through the implementation of a survey technique. Data were gathered via questionnaires administered to respondents TikTok users and have encountered Glad2Glow’s digital marketing content. Sampling technique was purposive sampling, with the respondent count established according to predetermined study criteria. The investigation utilized Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings demonstrate that testimonials have a significant effect on engagement and brand awareness, with engagement effectively mediating the relationship between testimonials and brand awareness. These findings indicate that genuine, experience-driven testimonials enhance audience engagement and bolster brand awareness. The study reveals that User Generated Content (UGC) does not significantly influence brand awareness, neither directly nor indirectly via engagement as a mediating variable. This suggests that broad or low-credibility user-generated content may inadequately facilitate meaningful connections and is insufficient for establishing robust brand perceptions in consumers' thoughts. The findings offer managerial insights for organizations to develop more effective digital marketing strategies by emphasizing credible testimonial-based material to improve brand awareness on social media platforms.